Fatalities in the construction industry: findings from a revision of the BLS Occupational Injury and Illness Classification System. - Xiuwen Dong; Largay, Julie A.; Xuanwen Wang; Windau, Janice A. (Monthly Labor Review, 2014)
Version 2.01 of the BLS Occupational Injury and Illness Classification System enables researchers to more readily identify factors that contribute to construction industry fatalities and provide the industry with insight into developing injury prevention strategies; the revision improves on current safety and health surveillance and will have long-term effects on safety and health intervention programs and policies targeted at both the construction industry and the overall U.S. workforce.